Cardiac Inflammatory Myofibroblastic Tumor in a Young Male Patient With Myopericarditis. Issue 25 (22nd December 2015) - Blanco, Miriam; Fulquet, Enrique; Laguna, Gregorio; Martínez, Gerardo; Sevilla, Teresa; Di Stefano, Salvatore; Ortega, Christian
Abstract : Supplemental Digital Content is available in the text.